Voltage-Mode Universal Biquadratic Filter Using Single DVCC. (10th March 2013) - Horng, Jiun-Wei; Jhao, Zih-Yang
Abstract : A voltage-mode universal biquadratic filter using a differential voltage current conveyor (DVCC), two capacitors, and two resistors is presented. The proposed circuit has four input terminals and three output terminals and can realize all the standard filter functions, which are lowpass, bandpass, highpass, notch, and allpass filters, without changing the circuit topology. Three simultaneous output filter responses can be obtained from some derived filter types. The proposed circuit employs only one DVCC that simplifies the configuration.